Penegakan Hukum Terhadap Praktik Pungutan Liar (Pungli) Dalam Penerbitan Kendaraan Bermotor - Litiloly, Haidin Ali Hamzah; Supusepa, Reimon (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Illegal levies (extortion) is an illegal practice in which officers collect money or other rewards illegally or violate the rules for an interest. This shows that extortion is a detrimental crime and must be eradicated to maintain justice and public trust. The aim of this research is to analyze and discuss law enforcement against police or traffic officers who practice illegal levies and analyze and discuss the obstacles to the practice of illegal levies.PurposesoftheResearch: The aim of this research is to analyze and discuss law enforcement against police or traffic officers who practice illegal levies and to analyze and discuss the obstacles to the practice of illegal levies.Methods of the Research: Research method with normative juridical research type. The problem approach used is a statutory approach, a conceptual analysis approach. Legal materials consist of primary, secondary and tertiary. Techniques for collecting legal materials through library research and qualitative analysis of legal materials.Results of the Research: The results of the research show that law enforcement against individual traffic police officers who practice illegal levies is still difficult to realize, this is because there are many obstacles encountered in the law enforcement process. Starting from the difficulty of proving the practice of illegal levies, the existence of witnesses and statements from victims of extortion, there is no law that regulates it explicitly. The results of further research are the obstacles in the practice of illegal levies, namely: The absence of a law that specifically regulates illegal levies, lack of community participation in reporting illegal levies, proof in the field which is very difficult, inadequate facilities and infrastructure, and lack of support. there are criminal sanctions imposed on the perpetrator.